From Rainforest to Cane Field in Cuba : An Environmental History since 1492 - Funes Monzote, Reinaldo, 1969- (Book collections on Project MUSE., 2008)
This environmental history of Cuba since the age of Columbus emphasises the two processes that have had the most dramatic impact on the island's landscape: deforestation and sugar cultivation. The book considers Cuba's vital sugar industry through the lens of environmental history. It demonstrates how the industry that came to define Cuba - and upon which Cuba urgently depended - also devastated the ecology of the island.